Analysis of The Implementation of ISPO Certification on Smallholder Oil Palm Plantation in Beringin Jaya Cooperation Koto Ringin Village Mempura Sub-District Siak District - Yusuf, M.; Hutabarat, Sakti; Hadi, Syaiful (Journal of Agribusiness and Community Empowerment (JACE), 2021)
ISPO certification for oil palm smallholders is based on four principles: plantation legality, smallholder organization and management, environmental management, and a commitment to continuous improvement. The goal of this study is to examine how ISPO standards are used in oil palm smallholder cooperatives and to develop an ISPO application strategy for relevant stakeholders. The research was carried out at the Beringin Jaya Cooperative in the Siak District. A survey method was used to collect primary data from direct interviews with planters and secondary data from government agencies. The total number of people who took part in this study was 66, and the respondents were chosen at random sampling. This study employs descriptive qualitative analysis as well as strategic SWOT matrices for strategic analysis. According to the findings, the cooperative follows 54.17 percents of ISPO standards or 26 out of 48 indicators. This research suggests some development strategies to meet ISPO standards, such as providing assistance and direction to smallholders through government agencies to avoid negative consequences during the certification process, technical assistance, agricultural counseling and training, government and financial institution funding, and the use of cooperatives, farmer groups, and mills to disseminate ISPO standards to farmers.